Capote - Miller, Bennett, 1966-; Mickelson, Allie; Kelci Stephenson; Philip Seymour Hoffman; Craig Archibald; Bronwen Coleman; Kate Shindle; David Wilson Barnes; Michael J Burg; Catherine Keener; Kwesi Ameyaw; Andrew Farago; et al. (USA United Artists, 2005)
In 1959, Truman Capote, a popular writer for The New Yorker, learns about the horrific and senseless murder of a family of four in Holcomb, Kansas. Inspired by the story material, Capote and his partner, Harper Lee, travel to the town to research for an article. However, as Capote digs deeper into the story, he is inspired to expand the project into what would be his greatest work, In Cold Blood. To that end, he arranges extensive interviews with the prisoners, especially with Perry Smith, a quiet and articulate man with a troubled history. As he works on his book, Capote feels some compassion for Perry which in part prompts him to help the prisoners to some degree. However, that feeling deeply conflicts with his need for closure for his book which only an execution can provide. That conflict and the mixed motives for both interviewer and subject make for a troubling experience that would produce an literary account that would redefine modern non-fiction.
On the night of 14 November 1959, in Holcomb, Kansas, a farmhouse is broken into by the criminals Perry Smith and Dick Hickock that expect to get US$ 10,000.00. With the policy of "no witness", the murderers kill the entire family. The homosexual writer Truman Capote travels to the small town with his friend Nelle Harper Lee and decide to use the topic to write a book. When the killers are arrested, he becomes friend of Perry for his own interest and then he falls in love for him, and gets a new lawyer for them, postponing their execution until 14 April 1965.
Languages: English, Polish Subtitles: English, Turkish, Polish, Hungarian, Czech, Serbo-Croatian, Arabic, Bulgarian, Danish, Finnish, Greek, Hebrew, Icelandic, Estonian, Lithuanian, Norwegian, Slovenian, Swedish, Romanian
Keywords: Biography; Crime; Drama